Precedent texts in advertisements - Aliūkaitė, Daiva; Amankevičiūtė, Simona (Lietuvių kalba, 2009)
The present paper discusses precedent texts in advertisements. A precedent text is defined as an axiological sign functioning within a semiotic space of culture. The precedent text is introduced into any text by giving the name of the author or the character or the title of a literary work or just quoting it. The precedent text is important for a person at the cognitive and emotive levels and is well-known within the person’s social environment (both of his/her own as well as previous generations); it is fore-grounded in the discourse each time it is generated by the linguistic person. The authors adhere to the view that an advertisement is a Creole text consisting of components of verbal and visual communication. The approach implies a possibility for other texts, i.e. precedent texts, to occur in the advertisement text. The paper focuses on the meaning and functionality of precedent texts in Lithuanian printed advertisements. The investigation into the diversity of precedent texts and their frequency in advertisements is based on the methodological instruments offered by cognitive linguistics and linguistic culturology. A limited scope of the material could only lead to very tentative conclusions on precedent texts in advertisements. The insights could be treated as prerequisites or hypotheses for further research. So in the discourse of advertising precedent texts tend to be quasi-quoted, there are also clear tendencies to make allusive references to precedent texts (precedent phenomena). The advertisements give preference to a mixed type of actualisation of the precedence phenomena. Undoubtedly, precedent advertisements, due to their appeal to the addressee’s cognitive basis, are much more suggestive than denotative advertisements, which are limited to the context of daily life. The interdependence between the functions of advertisements and precedent texts, especially the functions of game and password, facilitates the spread of the message of the advertisement and its preservation in the memories of addressees.